Zn(II) and Cd(II)-based complexes for probing the enzymatic hydrolysis of Na4P2O7 by alkaline phosphatase in physiological conditions - Das, Priyadip; Sourish, Bhattacharya; Sandhya, Mishra; Das, Amitava (Chemical Communications, 2011)
Newly synthesized Zn(II) and Cd(II)-based complexes show unique selectivity towards inorganic pyrophosphate (PPi) in 100% aqueous medium at pH = 7.4 and act as a "turn-on" and "turn-off" real-time assay, respectively, for the evaluation of the enzymatic activity of alkaline phosphatase.

ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.

Zn(II)-cyclam based chromogenic sensors for recognition of atp in aqueous solution under physiological conditions and their application as viable staining agents for microorganism - Mahato, Prasenjit; Ghosh, Amrita; Mishra, Sanjiv K.; Shrivastav, Anupama; Mishra, Sandhya; Das, Amitava (Inorganic Chemistry, 2011)
Two chromogenic complexes, L.Zn (where L is (E)-4-((4-(1,4,8,11-tetraazacyclotetradecan-1-ylsulfonyl)phenyl)diazenyl)-N,N-dimethylaniline) and its [2]pseudorotaxane form (α-CD.L.Zn), were found to bind preferentially to adenosine triphosphate (ATP), among all other common anions and biologically important phosphate (AMP, ADP, pyrophosphate, and phosphate) ions in aqueous HEPES buffer medium of pH 7.2. Studies with live cell cultures of prokaryotic microbes revealed that binding of these two reagents to intercellular ATP, produced in situ, could be used in delineating the Gram-positive and the Gram-negative bacteria. More importantly, these dyes were found to be nontoxic to living microbes (eukaryotes and prokaryotes) and could be used for studying the cell growth dynamics. Binding to these two viable staining agents to intercellular ATP was also confirmed by spectroscopic studies on cell growth in the presence of different respiratory inhibitors that influence the intercellular ATP generation.